Pharmacy practice in COVID-19 from a Middle Eastern and African perspective: A narrative review - Al-Saffar, Haider; Aljazzar, Rasha; Al-Saffar, Amina (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
The coronavirus disease 2019 (COVID-19) had a worldwide impact on all aspects of life and primarily on clinical practice involving all health-care professionals. Pharmacists are at the forefront of all clinical facilities in hospitals and the community. We aimed to provide a narrative overview of the global literature on the impact of COVID-19 changing roles and pharmacists' contribution to the overall clinical care during the COVID-19 pandemic. We conducted a narrative, nonsystematic review of the international literature from a single major medical online database, PubMed, between February 1, 2020, and June 30, 2021. The relevant articles were narrated in a concise thematic account. During the COVID-19 pandemic, pharmacists had to serve their responsibilities alongside other activities while the entire world was fighting an invisible virus. However, it was much more complicated than before because the novel coronavirus is intractable. There was no vaccine or established therapeutic guidelines when it manifested suddenly. As part of an interdisciplinary team, community pharmacists may carry out their responsibilities and play an essential role in disease control and management. However, they may need to be appropriately prepared, trained, and equipped to deal with pandemic and postpandemic situations.
Keywords: Community pharmacists; COVID-19; cross-sectional survey; education; extended roles; health care; health-care roles; hospital pharmacists; pandemic; pharmacy practice; prevention; surveys